The Influence of Financial Planning Literacy and Financial Inclusion on The Growth of Cafe Smes in Malang City - Priskalina Sartika Sudirman; Moch Nurhidayat; Noviana Yaniar Suprajitno (International Research & Development for Human Beings (IRDH), 2026)
This study aims to determine the effect of financial planning literacy and financial inclusion on the growth of Small and Medium Enterprises (SMEs) cafes in Malang City. Financial planning literacy is the ability of business actors to understand, plan, and manage business finances effectively, while financial inclusion relates to access and utilization of formal financial services such as banking and other financial institutions. This study uses a quantitative approach with descriptive and verification methods. The population in this study were all 144 SME cafe operators in Malang City, with a sample of 60 respondents determined using a purposive sampling technique. Data collection was carried out through a questionnaire with a Likert scale. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. The results of the study indicate that financial planning literacy and financial inclusion, both partially and simultaneously, have a positive and significant effect on the growth of SME cafes in Malang City. This indicates that the better the ability of business actors in financial planning and the wider access to formal financial services, the greater the growth of cafe businesses. Therefore, improving financial literacy and expanding access to formal financial services will further boost cafe business growth. Therefore, improving financial literacy and expanding access to financial services for SMEs are crucial factors in driving sustainable business development.